Pharmacological inhibition of mannose-binding lectin ameliorates neurobehavioral dysfunction following experimental traumatic brain injury. Issue 3 (March 2017) - De Blasio, Daiana; Fumagalli, Stefano; Longhi, Luca; Orsini, Franca; Palmioli, Alessandro; Stravalaci, Matteo; Vegliante, Gloria; Zanier, Elisa R; Bernardi, Anna; Gobbi, Marco; De Simoni, Maria-Grazia
Mannose-binding lectin is present in the contusion area of traumatic brain-injured patients and in that of traumatic brain-injured mice, where mannose-binding lectin-C exceeds mannose-binding lectin-A. The reduced susceptibility to traumatic brain injury of mannose-binding lectin double knock-out mice (mannose-binding lectin −/− ) when compared to wild type mice suggests that mannose-binding lectin may be a therapeutic target following traumatic brain injury. Here, we evaluated the effects of a multivalent glycomimetic mannose-binding lectin ligand, Polyman9, following traumatic brain injury in mice. In vitro surface plasmon resonance assay indicated that Polyman9 dose-dependently inhibits the binding to immobilized mannose residues of plasma mannose-binding lectin-C selectively over that of mannose-binding lectin-A. Male C57Bl/6 mice underwent sham/controlled cortical impact traumatic brain injury and intravenous treatment with Polyman9/saline. Ex-vivo surface plasmon resonance studies confirmed that Polyman9 effectively reduces the binding of plasma mannose-binding lectin-C to immobilized mannose residues. In vivo studies up to four weeks post injury, showed that Polyman9 induces significant improvement in sensorimotor deficits (by neuroscore and beam walk), promotes neurogenesis (73% increase in doublecortin immunoreactivity), and astrogliosis (28% increase in glial fibrillary acid protein). Polyman9 administration in brain-injured mannose-binding lectin −/− mice had no effect on post-traumatic brain-injured functional deficits, suggestive of the specificity of its neuroprotective effects. The neurobehavioral efficacy of Polyman9 implicates mannose-binding lectin-C as a novel therapeutic target for traumatic brain injury.